IMPLEMENTASI METODE ROLE PLAYING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMAN 2 KOTA BANJAR - Syifa Firahmatika; Rahman Afandi (Khulasah : Islamic Studies Journal, 2025)
In the educational context, teachers are afforded the flexibility to determine instructional models that are best suited to the conditions and characteristics of their students. The careful selection of an appropriate teaching approach is expected to create a conducive and engaging learning environment, thereby enabling students to comprehend, internalize, and master the material being delivered. One of the active learning methods used at SMAN 2 Banjar is the role-playing method. The role-playing method is an active learning method that involves students as active participants in the learning process. This study employs qualitative research methods, utilizing data collection techniques such as observation, interviews, and documentation. The results of the study indicate that the implementation of the Role Playing method in Islamic Education and Character Education at SMAN 2 Banjar, West Java, is divided into three main steps: the introductory phase, which includes the stages of selecting roles, outlining role stages, preparing observers, and selecting actors. The second step is the core activity, which includes the role-playing process, discussion, and evaluation. The final step is the closing activity, which involves sharing experiences and concluding. The outcomes achieved through the Role Playing learning method are: (1) creating a strong learning impression; (2) being enjoyable for students; (3) fostering a spirit of optimism; (4) students actively engaging in the learning process. Meanwhile, the challenges faced by teachers in implementing this learning method include limited learning time, the need for high teacher creativity, difficulty in managing the class, and the process of selecting appropriate lesson materials to be presented through the Role Playing method.